2020
DOI: 10.3389/fendo.2019.00873
|View full text |Cite
|
Sign up to set email alerts
|

The Association Between Serum Ferritin Concentration and Visceral Adiposity Estimated by Whole-Body DXA Scan in Women With Polycystic Ovary Syndrome

Abstract: Objective: Women with polycystic ovary syndrome (PCOS) are characterized by insulin resistance and higher prevalence of obesity. Serum ferritin is increased in obesity and is associated with insulin resistance. The aim of the present study was to evaluate the relationships between serum ferritin concentration with insulin resistance and body composition estimated by dual-energy X-ray absorptiometry (DXA) in PCOS women in comparison to the control group. Patients and Methods: One hundred four women were enrolle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 42 publications
0
19
0
Order By: Relevance
“…Furthermore, transferrin receptors colocalize with glucose transporters and insulin-like growth factor II receptors in the microsomal membranes of cultured adipocytes, suggesting that regulation of iron uptake by insulin occurs in parallel with its effects on glucose transport [ 109 ]. Indeed, obese people have increased iron levels [ 110 , 111 ] and become prone to IR and potentially harmful lipofuscinogenesis.…”
Section: Lipofuscin As a Novel Redox Biomarker Of Insulin-related Metabolic Diseasesmentioning
confidence: 99%
“…Furthermore, transferrin receptors colocalize with glucose transporters and insulin-like growth factor II receptors in the microsomal membranes of cultured adipocytes, suggesting that regulation of iron uptake by insulin occurs in parallel with its effects on glucose transport [ 109 ]. Indeed, obese people have increased iron levels [ 110 , 111 ] and become prone to IR and potentially harmful lipofuscinogenesis.…”
Section: Lipofuscin As a Novel Redox Biomarker Of Insulin-related Metabolic Diseasesmentioning
confidence: 99%
“…The concentrations of serum insulin, plasma glucose, total cholesterol (TC), high-density lipoprotein cholesterol (HDL-C), and triglycerides (TG) were measured as previously described (17). Plasma low-density lipoprotein cholesterol (LDL-C) was calculated with Friedewald's formula.…”
Section: Biochemical Analysesmentioning
confidence: 99%
“…Plasma low-density lipoprotein cholesterol (LDL-C) was calculated with Friedewald's formula. Luteinizing hormone (LH), FSH, prolactin (PRL), and sex hormone-binding globulin (SHBG) were assessed as previously described (17). Total testosterone concentration was assessed by radioimmunoassay (DIAsource ImmunoAssays S.A., Belgium); the minimum detectable concentration was 0.05 ng/ml, and the intra-assay and inter-assay coefficients of variation were estimated at 3.3 and 4.8%, respectively.…”
Section: Biochemical Analysesmentioning
confidence: 99%
“…The authors of this trial also found a positive correlation with triglycerides, insulin, and homeostatic model assessment, but not with BMI and WC. 19 Boemeck et al 20 found increased levels of ferritin (>322 ng/mL) in 80% of men and 8.7% of women in a study of patients with nonalcoholic fatty liver disease (NAFLD) but did not find significant differences between ferritin levels and adequate or inadequate NC. Neck circumference is a rapid and low-cost evaluation and may work as an anthropometric indicator that is not influenced by variations in some conditions, such as abdominal distension.…”
Section: Discussionmentioning
confidence: 98%